Kearifan Lokal Dan Pengetahuan Ibu Terhadap Status Gizi Dan Pola Makan Pada Kejadian Stunting Usia Preschool - Natalia, Elfina; Ping, Maria Floriana (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
The Ministry of Health (2015) conducted monitoring of nutritional status with the result that EastKalimantan had 26.7% of children who were stunted, of which 18.3% were classified as short and 8.4%were very short. Stunting is closely related to low nutrient intake due to inappropriate feeding behavior,this is influenced by maternal nutritional knowledge and local wisdom. This study aims to see therelationship and implications of local wisdom and knowledge of mothers on nutritional status and diet inpreschool age children. Using analytical observational methods with a combination of quantitative andqualitative methods with a number of respondents 50. Logistic regression test revealed that the dominantoccurrence of stunting is influenced by the mother's knowledge of nutrition with a value of p = 0.027 andOR = 3.801. Meanwhile, the qualitative data reveals that there is a misperception regarding growth anddevelopment in preschool age children. This analysis informs that the mother's mistaken knowledge andperceptions of nutrition have a close relationship with the incidence of stunting in preschool children.